The current practice of social work in pain management: a scoping review on chronic disease. (16th March 2021) - King, Jennifer; Tupper, Susan; Fletcher, Kara; Brose, Kelsey; Goodridge, Donna
ABSTRACT: While social workers have the capacity and scope of practice to make a significant contribution to pain management, little is understood about how they enact these roles. The initial goal of this scoping review was to examine the role of social work in pain management specifically in bleeding disorder care. Due to lack of published data on this topic, the review goal was broadened to chronic disease. Two electronic databases were searched providing a total of 13 published articles meeting the inclusion and exclusion criteria. Instrumental services, clinical services, and assessments were identified as primary roles of social workers, while advocacy, policy development, education, and skill development require further exploration in the literature.